ANALYSIS OF FINANCIAL PERFORMANCE BEFORE AND AFTER SPIN-OFF IN PT. BNI (PERSERO) TBK - Tanawal, Alfian Ryan Henry; Tumiwa, Johan (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2014)
Many company must have the own competitive advantage in order to survive in its environment, actually after the global economic crisis. To keep survive and living in that global competition, commonly every company has built their own strategies as well as gather a profit maximization. Over the past decade, merger, acquisition, spin-off and other forms of expansion in operations have declined sharply, and many conglomerates have resorted to downsizing and focusing their businesses on their core competencies Some corporate take the spin-off decision to gain the more benefit. The purpose of this research is to analyze whether there is significant difference on financial performance of PT. BNI Tbk (Persero) before and after spin-off with PT. BNI Syariah in 2010. This research is comparative study. This current research has used judgment sampling method. This research concern on BNI spin-off in 2010, and then the research needs three years data before and three years data after 2010. The Paired Samples T-Test is deployed to accomplish the research’s objectives. From nine variables that have been tested with this research’s tools, six of those variables show the significant different after BNI did spin-off, and three of them show there is no significant different. PT. BNI Tbk (Persero) should concern about a spin-off policy, since there is a significant difference on ROA, ROE, current ratio, CAR, OEOI and EPS before and after spin-off. Keywords: spin-off, financial, fundamental factor